Enabling a Freight Traffic Controller for Collaborative Multidrop Urban Logistics: Practical and Theoretical Challenges. Issue 1 (January 2017) - Allen, Julian; Bektaş, Tolga; Cherrett, Tom; Friday, Adrian; McLeod, Fraser; Piecyk, Maja; Piotrowska, Marzena; Austwick, Martin Zaltz
There is increasing interest in how horizontal collaboration between parcel carriers might help alleviate problems associated with last-mile logistics in congested urban centers. Through a detailed review of the literature on parcel logistics pertaining to collaboration, along with practical insights from carriers operating in the United Kingdom, this paper examines the challenges that will be faced in optimizing multi-carrier, multidrop collection, and delivery schedules. A "freight traffic controller" (FTC) concept is proposed. The FTC would be a trusted third party, assigned to equitably manage the work allocation between collaborating carriers and the passage of vehicles over the last mile when joint benefits to the parties could be achieved. Creating this FTC concept required a combinatorial optimization approach for evaluation of the many combinations of hub locations, network configuration, and routing options for vehicle or walking to find the true value of each potential collaboration. At the same time, the traffic, social, and environmental impacts of these activities had to be considered. Cooperative game theory is a way to investigate the formation of collaborations (or coalitions), and the analysis used in this study identified a significant shortfall in current applications of this theory to last-mile parcel logistics. Application of theory to urban freight logistics has, thus far, failed to account for critical concerns including ( a ) the mismatch of vehicle parking locations relative to actual delivery addresses; ( b ) the combination of deliveries with collections, requests for the latter often being received in real time during the round; and ( c ) the variability in travel times and route options attributable to traffic and road network conditions.